Chemoresistive Gas Sensors for Food Quality Monitoring - Lee, Seonyong; Kim, Seungsoo; Nam, Gi-Baek; Eom, Tae-Hoon; Jang, Ho Won (Journal of semiconductor technology and science, 2022)
The maintenance of food quality has become a crucial assignment to obstruct foodborne diseases in the pandemic era. Various methods have been utilized to monitor the freshness of foods, including gas chromatography-mass spectroscopy (GC-MS). However, most of such methods are not suitable for real-time food quality monitoring. Thus, chemoresistive gas sensors have gained high attention for in-situ monitoring of food quality due to their simple structure, small volume, and low price. Herein, we introduce highly efficient food quality monitoring using chemoresistive gas sensors based on metal oxides, metal sulfides, carbon nanomaterials, polymers, and their composites. We provide diverse strategies to improve the detection of food freshness, such as nanostructure construction and heterostructure formation. KCI Citation Count: 0